Penerapan Model PjBL Untuk Meningkatkan Kemampuan Komunikasi Pada Mata Pelajaran Matematika di SD Negeri 3 Patrol Lor - Puteri Apriani; Fikriyah Fikriyah; Susilawati Susilawati (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Learning carried out in class IV of SD Negeri 3 Patrol Lor was informed that class IV teachers tend to still use conventional learning models so that students' abilities in communication have not been well honed. The lack of a supportive learning model will affect communication skills, where in the 21st century students are required to have good communication. Given these problems, there needs to be improvements in learning, one of which is using the PjBL model so that students will be included in every step of learning. This research aims to determine the implementation of PjBL in class IV flat shape material and to determine whether there is an improvement or not in students' communication skills after using PjBL. This type of research uses Classroom Action Research (PTK). The subjects of this research were grade IV students at SD Negeri 3 Patrol Lor, Patrol District, Indramayu Regency. The types of research instruments used are observation, interviews, LKPD, and evaluation tests. The conclusion of this research is that there is an increase in students' communication skills from pre-cycle to cycle 2. The results of the pre-cycle were only 38.5% of students who were able to communicate. Then there was an increase in cycle 1 of students who were able to communicate to 57.7%. Then there was another improvement in cycle 2 and there was another increase of 88.5% of students who were able to communicate well, both with teachers and with friends. From these results it can be concluded that implementing a good PjBL model can improve students' communication skills well.